v.1 - Bhatnagar, A. S. (Hyderabad, 2011)
The Statutory Rules are in the nature of subordinate legislation. However, there are no other Statutory Rules, which enjoy such formidable position and which are subject matter of so much judicial scrutiny as Central Civil Services (Classification, Control and Appeal) Rules, 1965. Several thousand judgements are pronounced every year by High Courts and Central Administrative Tribunals all over the country as also the Supreme Court of India. In spite of so much case law, the certainty of the subject is still a distant future. Certain changes in circumstances of a case very often turn the table for the litigant pitted against the State.
Keywords: Central civil services classification control and appeal